LEARNERS’ AGENCY IN FOCUS: INTRODUCING THE 21ST CENTURY ACADEMIC WRITING PEDAGOGY IN INDONESIA - Lala Bumela Sudimantara (IAIN Syekh Nurjati Cirebon, 2021)
The notion of transformative learning has been echoed by the Indonesian government in the National Standard of Education (2020, 2015). A shift from the teacher-centric into the student-centric pedagogy is a prerequisite to trigger the learning transformation. However, in the field of English language teaching (ELT) in particular, there remains a firm reliance on the dogma of modern linguistics that positions linguistic description and grammatical mastery as the key for meaning-making mechanism. Consequently, such monolithic ELT pedagogy expects a steady compliance from the students in relation to learning, and thus learners’ creative agency was removed. This paper is a reflection on how the learning of academic writing unit was approached differently by using a multisensorial-multicognitive pedagogy as informed by neuroscience, thus breaking away from linguistics as the sole informing theory for learning language. This new academic writing pedagogy embraces language learning as a complex system, thus incorporating other bio-psychological components in learning such as rhythm, intonation, movement, emotion, and aesthetics. This paper highlights how these components were used creatively in the three innovative learning tools – Verbotonal Approach, Reading for Emotions, and Aesthetics – to support agentive learning practice in academic writing course. This new pedagogy was developed in a doctoral research project in an Australian university and was proven effective to help students transform their learning practices.